Association and predictive value of Non-HDL-C, ApoB, and LDL-C with metabolic syndrome among adult rural Uyghur residents: a cross-sectional survey in Xinjiang Uygur Autonomous Region - Shipeng GAO; Shuxia GUO; Yu LI; Rulin MA; Heng GUO; Yunhua HU; Mulatibieke KEERMAN; Xianghui ZHANG; Xinping WANG; Yangbo ZHOU; Jiali LIAO; Jia HE (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo explore the association and predictive value of non-high-density lipoprotein cholesterol (Non-HDL-C), apolipoprotein B (ApoB) and low-density lipoprotein cholesterol (LDL-C) with metabolic syndrome (MS) in adult rural residents of Xinjiang Uygur Autonomous Region for facilitating early identification and prevention of MS in the residents. MethodsThe study enrolled 6 500 Uygur residents aged ≥ 18 years from 12 villages in the Kashgar region of Xinjiang Uygur Autonomous Region (Xinjiang) using a multistage random cluster sampling method. Face-to-face interviews were conducted during July-August 2017 using a self-designed questionnaire, along with physical examinations and laboratory tests. Unconditional multivariate logistic regression analysis and receiver operating characteristic (ROC) curve analysis were employed to assess the association between Non-HDL-C, ApoB, and LDL-C with MS, as well as to evaluate their predictive value for MS. ResultsThe analysis finally included a total of 5 156 participants, among whom 885 (17.2%) were identified as having MS. After adjusting for potential confounding factors including gender, age, education, smoking status, alcohol consumption, and body mass index, the results of multivariate unconditional logistic regression analysis revealed a significantly increased risk of MS among participants in the highest quartile of Non-HDL-C levels (odds ratio [OR] = 1.764; 95% confidence interval [CI]: 1.350 - 2.305). Similarly, participants in the third and highest quartiles of ApoB had a higher risk compared to those in the lowest quartile (OR = 1.372; 95%CI: 1.048 - 1.798 and OR = 1.645; 95%CI: 1.273 - 2.124 respectively). Additionally, individuals in the highest quartile of LDL-C had an elevated risk compared to those in the lowest quartile (OR = 1.403; 95%CI: 1.080 - 1.823). The receiver operating characteristic (ROC) analysis results revealed that Non-HDL-C, ApoB, and LDL-C had area under the curve (AUC) values of 0.654 (95%CI: 0.641 - 0.667), 0.608 (95%CI: 0.595 - 0.622), and 0.612 (95%CI: 0.592 - 0.633), respectively, as diagnostic indicators for metabolic syndrome in the study participants. Furthermore, Non-HDL-C demonstrated a significantly higher AUC compared to both ApoB and LDL-C (both P < 0.05). ConclusionThe prevalence of MS is relatively high among adult Uygur residents in rural Xinjiang, and Non-HDL-C demonstrates a stronger correlation and predictive value for MS compared to ApoB and LDL-C.